STUDI ATAS PEMIKIRAN ASGHAR ALI ENGINEER RELEVANSI NAFKAH BAGI MANTAN ISTRI - Syamsuri Syamsuri; Moh Hodri (Fakultas Agama Islam Universitas Nurul Jadid, 2022)
When a divorce occurs between a husband and wife, it creates obligations that must be obeyed by a husband and wife, and these obligations include an ex-husband being obliged to give a gift that must be given to the ex-wife who has been divorced, the gift is in accordance with economic conditions. the ex-husband (according to his ability), the provider of a living is a consolation during the 'iddah period, in Islamic law the provision of a living is only during the 'iddah period, this is different from Asghar's opinion, according to him the provision of a living for a divorced ex-wife, not only only during the 'iddah period, but until they remarry or die. The results of the study concluded that the criteria for women who are entitled to a sustainable living from their ex-husband are for women who are unable to take care of themselves (poor), because they do not have family or relatives, because it is far from a sense of justice if a woman who has divorced back to his parents or to his relatives. Asghar Ali Engineer's thoughts have relevance to Law Number 1 of 1974 article 41 letter (c). This of course also has implications for KHI, which only provides a living for the ex-wife only until the 'iddah period, and providing a living for the ex-wife who has been divorced can be given but by looking at these various criteria.